2017
DOI: 10.21511/ins.08(1).2017.02
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing diversification effect: evidence from the U.S. property-liability insurance industry

Abstract: Prior literature suggests that diversified property-liability (P/L) insurers underperform their focused counterparts. While most studies focus on insurers’ overall performance, there is an absence of evidence regarding whether the underperformance is driven by underwriting or investment profitability. The authors develop and test hypotheses of diversification’s separate effect on underwriting and investing in the U.S. property-liability (P/L) insurance industry. It is found that diversified insurers outperform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Ai et al (2018) found significant positive effect on firm performance. Che et al (2017) also found that in terms of return on investment the performance of diversified firms is better as compared to nondiversified firms, but diversified firms underperform than non-diversified firms with respect to underwriting profitability.…”
Section: Why Diversifymentioning
confidence: 90%
See 1 more Smart Citation
“…Ai et al (2018) found significant positive effect on firm performance. Che et al (2017) also found that in terms of return on investment the performance of diversified firms is better as compared to nondiversified firms, but diversified firms underperform than non-diversified firms with respect to underwriting profitability.…”
Section: Why Diversifymentioning
confidence: 90%
“…The benefits of diversification can be realized if the internal governance mechanisms are efficient (Williamson, 1985). In literature, product diversification has been analyzed with respect to property-liability or life-health insurance companies or companies that diversify across both types (Meador, Ryan & Schellhorn, 2000;Hardwick and Adams, 2002;Cummins, Weiss, Xie & Zi, 2010;Shim, 2011;Che, Liebenberg, Liebenberg & Powell;Ai, Bajtelsmit & Wang 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since the probability of its happening and non-happening are doubtful, it can be termed as a natural uncertainty. To deal with such mishaps, firms rely on various insurance contracts (Che, Liebenberg, Liebenberg, & Powell, 2017), employ risk mitigation techniques, and initiate prior preventive measures to reduce the impact of such events (Park, Hong, & Roh, 2013). The financial and economic risks identified as a second category in the above section are managed and controlled by the use of financial derivatives (Stulz, 2003).…”
Section: Corporate Risk Management and Firm Riskmentioning
confidence: 99%
“…The authors find evidence that undiversified insurers consistently outperform diversified insurers, and they estimate the diversification penalty to be 1% of return on assets or 2% of return on equity. Overall, existing academic research focusing on US insurers finds mixed results on the impact of diversification on firm performance (e.g., Ai et al, 2018; Berger & Ofek, 1995; Berry‐Stölzle et al, 2013; Che et al, 2017; Elango et al, 2008; Lamm‐Tennant & Starks, 1993; Mayers & Smith, 1990).…”
Section: Development Of Hypothesesmentioning
confidence: 99%